2020
DOI: 10.1111/jce.14341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the inflammation on the outcomes of catheter ablation of drug‐refractory ventricular tachycardia in cardiac sarcoidosis

Abstract: Introduction Catheter ablation (CA) of ventricular tachycardia (VT) in cardiac sarcoidosis (CS) has been reported with varying success. However, there is a scarcity of data on the outcomes of CA based on ongoing inflammation. Objective We hypothesized that the response to VT ablation depends upon the stage of the disease. Methods Between July 2004 and December 2018, 24 patients of CS presented with drug‐refractory VT at CARE Hospital (Hyderabad) and the University of Minnesota (Minneapolis, MN). Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Muser and colleagues 34 showed that a positive baseline FDG-PET scan led to an almost 4-fold increased rate of events in follow-up, primarily VT recurrence. Similarly Kaur and colleagues 57 showed that among patients in the inflammatory phase, 10 out of 17 had a recurrence of VT (58.8%), while only 1 out of 7 patients in the scar phase had VT recurrence over a mean follow-up of 5.7 ± 3.9 years. These findings suggest the importance of optimizing steroids/IST for control of VT prior to ablation.…”
Section: Results and Predictors Of Outcomementioning
confidence: 83%
See 3 more Smart Citations
“…Muser and colleagues 34 showed that a positive baseline FDG-PET scan led to an almost 4-fold increased rate of events in follow-up, primarily VT recurrence. Similarly Kaur and colleagues 57 showed that among patients in the inflammatory phase, 10 out of 17 had a recurrence of VT (58.8%), while only 1 out of 7 patients in the scar phase had VT recurrence over a mean follow-up of 5.7 ± 3.9 years. These findings suggest the importance of optimizing steroids/IST for control of VT prior to ablation.…”
Section: Results and Predictors Of Outcomementioning
confidence: 83%
“…34 Similarly Kaur and showed that aamongst patients in the inflammatory phase 10 out of 17 patients had a recurrence of VT (58.8%), while only one out of seven patients in the scar phase had VT recurrence over a mean follow-up of 5.7 +/-3.9 years These findings suggest the importance of optimizing steroids / immunosuppressive therapy for control of ventricular tachycardia prior to ablation. 57…”
Section: Results and Predictors Of Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Although CS confers a substrate for reentrant VT, catheter ablation can be challenging due to the complexity of substrates with multiple circuits and subepicardial locations likely requiring an epicardial ablation [49][50][51][52]. Besides, catheter ablation has been shown to have a lower likelihood for acute success and a higher recurrence rate if performed in the inflammatory phase compared to the healed phase [50•].…”
Section: Catheter Ablationmentioning
confidence: 99%